ANALISIS AUDIT REPORT LAG: Dampak Pergantian Manajemen, Kompleksitas Operasional, dan Ukuran Perusahaan pada Consumer Non-Cyclicals di BEI (2019-2022) - Damayanti, Riska (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The purpose of this research is (1) to determine the effect of management changes, complexity of company operations, KAP size together on audit report lag. (2) to determine the effect of management changes on audit report lag. (3) to determine the effect of company operational complexity on audit report lag. (4) to determine the effect of KAP size on audit report lag. This research is research that uses a quantitative approach. Furthermore, this research is a type of associative research. The data collection technique is a purposive sampling method. The data analysis methods in this research are descriptive statistical tests, research model tests, classical assumption tests, panel data regression tests and hypothesis tests. The results in this research are as follows: (1) management changes, complexity of company operations, KAP size together have a significant effect on. (2) change of management does not have a significant effect on audit report lag. (3) the complexity of company operations has a significant effect on audit report lag. (4) KAP size has a significant effect on audit report lag.